(untitled) (Philadelphia, 1986)
Edo Culture presents a selection of Nishiyama’s writings that serves not only to provide an excellent introduction to Tokugawa cultural history but also to fill many gaps in our knowledge of the daily life and diversions of the urban populace of the time. Many essays focus on the most important theme of Nishiyama’s work: the seventeenth to nineteenth centuries as a time of appropriation and development of Japan’s culture by its urban commoners
Keywords: Giải phẫu,Surgery; Các kỳ thi, câu hỏi, v.v ...,Examinations, questions, etc